Association between acupuncture treatment exposure and mortality in patients with heart failure: a nationwide cohort study - Jun, Hyungsun; Jin, Hanbit; Kim, Haerim; Leem, Jungtae (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPatients with heart failure (HF) require continuous management, creating a need for alternative treatments to reduce mortality. In Korea, acupuncture treatment is covered by national health insurance, offering accessible care without financial burden. Hence, this study utilized claims data from the Korean National Health Insurance Service to examine the association between acupuncture exposure and mortality in patients with HF.MethodsAdults aged 20 years or older with newly diagnosed HF were included. Patients who received two or more acupuncture sessions within one year of diagnosis comprised the acupuncture treatment-exposed group (AT group), while those who received none were classified as the non-exposed group (non-AT group). Propensity score matching was used to generate a balanced 1:1 matched cohort. From one year after diagnosis, the study tracked circulatory and all-cause mortality over a five-year period, performing survival and dose-response analyses.ResultsEach group included 4,315 patients, and the AT group showed significantly lower adjusted hazard ratios (aHRs) for circulatory disease-related mortality (0.79; 95% CI: 0.67–0.94) and all-cause mortality (0.73; 95% CI: 0.66–0.81). A clear dose-response relationship was observed, with greater exposure to acupuncture associated with lower aHRs.DiscussionAcupuncture within one year of HF diagnosis correlated with lower mortality from circulatory diseases and all causes. Future studies should adopt prospective and methodologically rigorous designs to validate the findings of this study.